Cam Jansen and the Valentine baby mystery / 25. - Adler, David A. (Adler, David A. Cam Jansen adventure, 2005)
Using her photographic memory Cam Jansen joins Eric in solving the mystery of a Valentine's day robbery in a hospital waiting room.